Potential Contribution of Ultrasonography Assistance for the Safe and Steady Procedure of Endoscopic Intracerebral Hematoma Evacuation: A Retrospective Cohort Study - Kitamura, Yuki; Kawaguchi, Tomohiro; Uchida, Hiroki; Endo, Hidenori; Tominaga, Teiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Endoscopic hematoma evacuation is one of the most promising procedures for the treatment of intracerebral hemorrhage (ICH) to avoid severe outcomes, such as death or dependency. However, the effect of the procedure on the functional outcome remains controversial. Thus, standardization and sophistication are required to enhance the surgical results. This study aimed to evaluate the potential efficacy of ultrasonography (US) in endoscopic hematoma evacuation.methods This study included 39 consecutive patients with spontaneous supratentorial ICH who underwent endoscopic hematoma evacuation between April 2019 and July 2021. The patients were divided into two groups, namely, surgery with or without US assistance. Rebleeding and evacuation rate were set as the primary endpoints, and operation time, requirement for repeat puncture, and modified Rankin scale at discharge were set as the secondary endpoints. During surgery, the burr hole was placed, and the dura mater was widely opened. The US probe was applied on the brain surface via the burr hole to detect the depth and direction of the hematoma cavity. With US assistance, the hematoma cavity was punctured with a cannula, and the transparent port was introduced into the hematoma cavity along the tract. The hematoma was gently evacuated with the irrigation–suction instrument.Results Of the 39 cases, 9 underwent endoscopic hematoma evacuation with US assistance. Rebleeding was noted in 0 and 2 (6.7%) patients with and without US assistance, respectively (p = 0.43). The mean hematoma evacuation rates were 78.6 and 80.6% in patients with and without US assistance, respectively (p = 0.80). In all cases with US assistance, the cavity could be reached with a single tap. However, repeat puncture was required in 20 (66.7%) cases without US assistance (p = 0.04). In one case, an unexpected residual hematoma was detected using US, which was applied after hematoma evacuation and before wound closure. The operation time was not extended even if US was used during the surgery.Conclusions US-assisted hematoma evacuation is an effective procedure that can assist in the precise insertion of the puncture cannula and exclusion of the residual hematoma. US might contribute toward improving the accuracy of each step of the procedure, thus leading to better clinical outcomes.
Keywords: endoscopic surgery; hematoma evacuation; intracerebral hematoma; ultrasonography